Zinc binding groups for histone deacetylase inhibitors - Lei Zhang; Jian Zhang; Qixiao Jiang; Li Zhang; Weiguo Song (Taylor & Francis Group, 2018)
Zinc binding groups (ZBGs) play a crucial role in targeting histone deacetylase inhibitors (HDACIs) to the active site of histone deacetylases (HDACs), thus determining the potency of HDACIs. Due to the high affinity to the zinc ion, hydroxamic acid is the most commonly used ZBG in the structure of HDACs. An alternative ZBG is benzamide group, which features excellent inhibitory selectivity for class I HDACs. Various ZBGs have been designed and tested to improve the activity and selectivity of HDACIs, and to overcome the pharmacokinetic limitations of current HDACIs. Herein, different kinds of ZBGs are reviewed and their features have been discussed for further design of HDACIs.